The Historical Approach in Muhammad Arkoun's Thought: Its Relevance to the Study of Contemporary Islamic Civilization History - Nofrianti, Mami; Mardianto, Pisdoni; Fithri, Widia (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2025)
This paper discusses the historical approach in Muhammad Arkoun's thinking. It aims to reveal and analyze the historical approach in Muhammad Arkoun's thinking and explain its relevance to the development of contemporary Islamic Civilization History studies. This research stems from concerns about the normative and apologetic tendencies in Islamic historical writing, which necessitate a more contextual and rational critical reading. It uses a qualitative method based on literature study, specifically library research. Data was collected through searching primary and secondary sources in the form of Muhammad Arkoun's works, books, scientific articles, and relevant academic writings. Data analysis was carried out through content analysis in three stages: (1) data reduction, namely selecting and classifying the main concepts in Arkoun's thinking; (2) data presentation, by describing the findings in accordance with the frameworks of historicity, deconstruction, and interdisciplinary approaches; and (3) drawing conclusions, to assess the relevance of Arkoun's thoughts to the study of contemporary Islamic Civilization History. The results of the study show that Arkoun's thinking produced five important findings. First, the concept of textual historicity offers a new paradigm in reading Islam as an evolving socio-cultural construct, rather than a frozen dogma. Second, the deconstruction of classical Islamic historiography opens up space for criticism of ideological historical narratives and opens up opportunities for alternative historical writing from the perspective of marginalized groups. Third, Arkoun integrates the humanities—such as anthropology, linguistics, and philosophy—as the basis for an interdisciplinary approach to the study of Islam. Fourth, his thinking provides a new methodological model for education and research in Islamic Civilization History, namely Islamic history as a reflective discourse that interprets the social and cultural dynamics of the ummah. Fifth, Arkoun's historical approach became an instrument of religious reasoning reform, encouraging a transformation from closed reasoning (la raison close) to open reasoning (la raison ouverte) that is rational, dialogical, and contextual. Thus, the historical approach in Arkoun's thinking is not only a critique of classical Islamic historiography, but also provides a new direction for epistemological, methodological, and paradigmatic renewal in the development of Islamic Civilization History studies in the modern era. Tulisan ini membahas pendekatan sejarah dalam pemikiran Muhammad Arkoun. Tulisan ini bertujuan untuk mengungkap dan menganalisis pendekatan sejarah dalam pemikiran Muhammad Arkoun serta menjelaskan relevansinya bagi pengembangan studi Sejarah Peradaban Islam kontemporer. Penelitian ini berangkat dari kegelisahan atas kecenderungan penulisan sejarah Islam yang normatif dan apologetik, sehingga diperlukan pembacaan kritis yang lebih kontekstual dan rasional. Melalui metode kualitatif berbasis studi literatur, jenis penelitian kepustakaan (library research). Data dikumpulkan melalui penelusuran sumber-sumber primer dan sekunder berupa karya-karya Muhammad Arkoun, buku, artikel ilmiah, dan tulisan-tulisan akademik yang relevan. Analisis data dilakukan melalui analisis isi (content analysis) dengan tiga tahap: (1) reduksi data, yakni memilih dan mengklasifikasi konsep-konsep utama dalam pemikiran Arkoun; (2) penyajian data, dengan menguraikan temuan sesuai kerangka historisitas, dekonstruksi, dan pendekatan interdisipliner; dan (3) penarikan kesimpulan, untuk menilai relevansi pemikiran Arkoun terhadap studi Sejarah Peradaban Islam kontemporer. Hasil kajian menunjukkan bahwa pemikiran Arkoun menghasilkan lima temuan penting. Pertama, konsep historisitas teks menawarkan paradigma baru dalam membaca Islam sebagai konstruksi sosial-budaya yang terus berkembang, bukan dogma yang beku. Kedua, dekonstruksi historiografi Islam klasik membuka ruang kritik terhadap narasi sejarah yang ideologis dan membuka peluang penulisan sejarah alternatif dari perspektif kelompok terpinggirkan. Ketiga, Arkoun mengintegrasikan ilmu-ilmu humaniora—seperti antropologi, linguistik, dan filsafat—sebagai landasan pendekatan interdisipliner dalam studi Islam. Keempat, pemikirannya menyediakan model metodologis baru bagi pendidikan dan riset Sejarah Peradaban Islam, yaitu sejarah Islam sebagai wacana reflektif yang menafsirkan dinamika sosial dan budaya umat. Kelima, pendekatan historis Arkoun menjadi instrumen reformasi nalar keagamaan, mendorong transformasi dari nalar tertutup (la raison close) menuju nalar terbuka (la raison ouverte) yang rasional, dialogis, dan kontekstual. Dengan demikian, pendekatan sejarah dalam pemikiran Arkoun tidak hanya bersifat kritik terhadap historiografi Islam klasik, tetapi juga memberikan arah baru bagi pembaruan epistemologis, metodologis, dan paradigmatik dalam pengembangan studi Sejarah Peradaban Islam di era modern.